Proceedings of the Eighth Symposium on Usable Privacy and Security 2012
DOI: 10.1145/2335356.2335358
|View full text |Cite
|
Sign up to set email alerts
|

Measuring user confidence in smartphone security and privacy

Abstract: In order to direct and build an effective, secure mobile ecosystem, we must first understand user attitudes toward security and privacy for smartphones and how they may differ from attitudes toward more traditional computing systems. What are users' comfort levels in performing different tasks? How do users select applications? What are their overall perceptions of the platform? This understanding will help inform the design of more secure smartphones that will enable users to safely and confidently benefit fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
183
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(194 citation statements)
references
References 21 publications
(15 reference statements)
7
183
1
3
Order By: Relevance
“…A considerable number of studies concerning user behavior, with regards to selecting and installing applications on smartphones, have found that users do not consider security and privacy issues during app selection, as they tend to ignore privacy policies and EULAs (End-user license agreement) [4]. Furthermore, Android users were found not to pay attention, understand, and act on permission information during installation [5,6].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable number of studies concerning user behavior, with regards to selecting and installing applications on smartphones, have found that users do not consider security and privacy issues during app selection, as they tend to ignore privacy policies and EULAs (End-user license agreement) [4]. Furthermore, Android users were found not to pay attention, understand, and act on permission information during installation [5,6].…”
Section: Related Workmentioning
confidence: 99%
“…A common argument towards the reviewed studies is that, although they address a similar topic, they are geographically limited [11][12][13] or they investigate behaviors in relation to subsets of technologies [5,6,9] and problems [4,[7][8][9] that are not specifically related to the digital natives. Ariu et al [14] have worked on filling this gap by studying the level of awareness and perception of IT security amongst university students, paying particular attention to the world of mobile devices.…”
Section: Related Workmentioning
confidence: 99%
“…Privacy rating is just one aspect among many other attributes of an app whereas the user rating reflects how general audience holistically thinks about the app based on their individual experiences. Furthermore, people self-reported [8,11,12] that they consider privacy-related information far less important than user ratings in making app choices. Therefore, we considered the effect of the privacy rating in conjunction with the user rating.…”
Section: Fig 1 Visual Framing Positively-framed Visuals Of a Ratinmentioning
confidence: 99%
“…Application updates might be a potential way to implant new security vulnerability and privacy data leaks to the user's phones. Chin et al [17] studied users's confidence in security and privacy of Android. They found that users reported various concerns because of some misconceptions or misunderstandings.…”
Section: Update Behavior Of Androidmentioning
confidence: 99%